Chronic Venous Disease and Its Intersections With Diabetes Mellitus - Jarošíková, R; Roztočil, K; Husáková, J; Dubský, M; Bém, R; Wosková, V; Fejfarová, V (Physiological research, 2023)
Chronic venous disease (CVD) is a vascular disorder in which blood return is severely compromised and CVD is usually characterized by venous hypertension. Along with obesity and diabetes mellitus, CVD is one of the most common civilization diseases. In general, the estimated prevalence of CVD ranges from 60-80 %. Early diagnosis and adequate treatment are important for preventing progression to more severe stages of the disease like venous leg ulcers. Clinical manifestations of CVD in initial stages of the disease are often asymptomatic. However, as CVD progresses, symptoms begin to develop. Treatment of CVD could be divided into conservative and surgical. Conservative therapy consists of compression, pharmacological treatment and lifestyle change. In cases where conservative therapy is ineffective, surgical or endovascular treatment may be required. The intersections between diabetes mellitus (DM) and CVD are not to be underestimated. CVD and DM have often the same risk factors. Symptoms of CVD can be modified by late complications of DM, but the incidence of different CVD degrees seems to be the same as in diabetics as in non-diabetics population. We are particularly concerned in diabetics about worse compliance with treatment due to their often-poorer adherence to treatment of DM and lifestyle changes. Moreover, there exist a higher risk of CVD and peripheral arterial disease in diabetics patients. Patients with CVD should always be inspected for the presence of DM, considering its presence can have a bearing on CVD symptoms, diagnostic procedures, and therapeutic strategies.
Keywords: Vascular Diseases; Humans; chronická nemoc; nemoci cév; rizikové faktory; lidé; Cardiovascular Diseases; Risk Factors; kardiovaskulární nemoci; diabetes mellitus; Diabetes Mellitus; Chronic Disease